Customer Focus Strategy in the Digital Era: The Influence of AI Implementation and Competitive Advantage on Enhancing Brand Loyalty in Edutech Platforms - Ravindra Safitra Hidayat; Panca Maulana; Eryco Muhdaliha; Julian Bongsoikrama; Feby Lukito Wibowo (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the role of customer focus strategy in the digital era, emphasizing how artificial intelligence (AI) implementation shapes competitive advantage and brand loyalty in Edutech platforms. As digital transformation accelerates, adopting customer-centered approaches becomes vital for delivering personalized and relevant learning experiences. Employing a mixed-methods design, this research integrates quantitative and qualitative data from Edutech users. The findings reveal that artificial intelligence (AI)-driven strategies significantly enhance personalization of learning content, improve responsiveness, and strengthen user engagement, which in turn increases brand loyalty. Moreover, organizations that strategically embed AI gain a sustainable competitive advantage by achieving higher operational efficiency and adaptive service delivery. These insights highlight the strategic importance of positioning AI as a core element of customer focus strategy in digital education. The study also provides practical implications for Edutech providers aiming to build stronger customer relationships, foster user satisfaction, and ensure long-term loyalty in a competitive marketplace.